An Analytical Network Process on Financial Access of the Small and Medium Enterprise in Sharia Banking in Tasikmalaya City - Asep Suryanto; Fatimah Zahra Nasution (International Journal of Nusantara Islam, 2015)
Small and Medium Enterprise (SME) is one of the significant roles in national economic development. It is seemly followed by the rise of employment absorbent and equity in income distribution. The capital constraint and the impedance of banking financial access have become the main problem to the Small and Medium entrepreneurs. The objectives of this research are to identify the main factors as problems of Small and Medium Enterprises in having access to the financial institutions, and also to find out the solutions of the research problems. This research uses qualitative approach i.e. Analytic Network Process (ANP). Through applying this method, it is expected to help the researchers in making measurement and synthesis of some factors regarding on the topic analyzed as well as finding the solution for problems faced by the SMEs. The resources of the data is derived from questionnaires and in-depth interview with experts, practitioners, SMEs and regulators which then analyzed by the structure and hierarchy into homogen clusters of the SMEs problems and solutions, measuring into ratio scale and building synthesis. As the result, it becomes clear what factors impeding the financial access of the SMEs to banks. The results of this research show that the difficulties of SMEs in accessing financial support in Islamic financial institutions are internal problems of Islamic banking i.e. lack of financial assistance given to the SMEs, the functions of Islamic banking as business partners for SMEs is not optimal. Whereas the external problems in the SMEs are the disability in meeting the financial requirements asked by Islamic banking that are collateral and business history. The internal solutions are Islamic banking must give business mentoring to SMEs that have received financial supports to minimalize the bad credits level. The external solution is the government must also socialize Islamic financial mechanism to SMEs as part of education efforts.